Analisa Resiko Ergonomi Untuk Mengurangi Cidera Otot Pada Proses Barcode Material Dengan Menggunakan Metode Nordic Body Map dan Rapid Entire Body Assesment Pada PT. Shindengen Indonesia - Widya, Adi Rusdi; Sari, Putri Anggun; Anggara, Muhammad Hatta Ari (JURNAL TEKNIK INDUSTRI, 2023)
This study was conducted at PT. Shindengen Indonesia, there is a position problem that does not fit ergonomics while working so that various muscle complaints are found in workers and it affects the output produced. This investigation is to find out the stages of ergonomic risk and objective description of MSD complaints experienced by workers. This research was carried out by observing and giving questionnaires using the Nordic Body Map (NBM) method for workers in the Barcode Material section, the results obtained have a Moderate risk stage with a score of 57. Meanwhile, using the Rapid Entire Body Assessment (REBA) method for material bar code workers. The results obtained have a high risk stage with a score (9) on the activity of transferring materials to the trolley. The subjective MSD complaint that is most often felt is in the waist and neck, because of this, companies need to make SOPs that consider ergonomic aspects and need to add work facilities in the form of tables and trolleys that have a high height with workers.